Assessments of natural radioactivity and radiological hazards in construction materials used in Elazig, Turkey - Baykara, Oktay; Karatepe, Sule; Dogru, Mahmut (Pergamon-Elsevier Science Ltd, 2011)
Building materials contain natural radionuclides (U-238, Th-232 and K-40) and therefore cause direct radiation exposure to the public. The radioactivity content of samples obtained from building materials produced in Elazig city, East Anatolian of Turkey, have been analyzed by gamma-ray spectrometry. However, radium equivalent activities, total and annual effective dose rate and external (gamma), internal (alpha) hazard indexes were calculated and radon concentration, radon specific exhalation rate and effective radium content were measured. Also, indoor radon measurements carried out in each floor (uninhabited) of rough construction (newly construction). The specific concentrations of U-238, Th-232 and K-40, from selected building materials, ranged from 3.5 to 114.1 Bq/kg, 1.6-20.7 Bq/kg and 201.4-4928.0 Bq/kg, respectively. The lowest of Ra-eq is 36.5 +/- 1.8 Bq/kg calculated in bricks while the highest value is 405.2 +/- 20.9 Bq/kg in gas concrete. The average indoor radon concentration is 364.3 Bqm(-3), which is higher than the global mean value, in newly constructed floor. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Natural radioactivity; Gamma dose; Indoor radon; Building material